What a delay in Singapore’s political succession portends - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2020)
In a commentary, SMU Associate Professor of Law Eugene Tan discussed what a delay in Singapore’s political succession arising from the COVID-19 crisis might portend and explained the impact of such a move.